2005
DOI: 10.1897/04-260r.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long contact times on sediment sorption kinetics of spiked chlorinated compounds

Abstract: The desorption kinetics of hexachlorobenzene (HCB) and 2,4,4'-trichlororbiphenyl (PCB 28) spiked to a field sediment were studied using a gas-purge technique. A contact time of up to 1,461 d was used to assess long-term changes in desorption kinetics. Purge-induced desorption experiments lasted from 300 to more than 4,000 h. Fast-, slow-, and very-slow-desorbing fractions could be distinguished. The desorption patterns changed with contact time from mainly fast- and slow-desorbing fractions toward the dominati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…The times to equilibrium in Table 2 indicate that equilibrium would have been reached in approximately 1 to 6 d. The trend in the data for increasing chlorination further suggests that the time to equilibrium for higher‐chlorinated benzenes and PCBs is less than 1 day. That supports our earlier finding [8] that domination of very slowly desorbing fractions not only may occur on long contact times but also may be diminished by reduced availability of sites. In that study, it was observed that an additional spike of hexachlorobenzene, 2,4,4′‐trichlorobi‐phenyl, 2,4,6‐trichlorobiphenyl, and 2,2′,4,5′‐tetrachlorobi‐phenyl to a Ketelmeer sediment (not heated at 375°C as in the present study) purged for more than 4,000 h resulted in these sorbates being almost exclusively in the very slow desorbing domain, whereas spiking the sediment with some of these compounds before the gas purge resulted in sorbates being predominantly in the rapidly desorbing domain instead.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The times to equilibrium in Table 2 indicate that equilibrium would have been reached in approximately 1 to 6 d. The trend in the data for increasing chlorination further suggests that the time to equilibrium for higher‐chlorinated benzenes and PCBs is less than 1 day. That supports our earlier finding [8] that domination of very slowly desorbing fractions not only may occur on long contact times but also may be diminished by reduced availability of sites. In that study, it was observed that an additional spike of hexachlorobenzene, 2,4,4′‐trichlorobi‐phenyl, 2,4,6‐trichlorobiphenyl, and 2,2′,4,5′‐tetrachlorobi‐phenyl to a Ketelmeer sediment (not heated at 375°C as in the present study) purged for more than 4,000 h resulted in these sorbates being almost exclusively in the very slow desorbing domain, whereas spiking the sediment with some of these compounds before the gas purge resulted in sorbates being predominantly in the rapidly desorbing domain instead.…”
Section: Resultssupporting
confidence: 93%
“…Recently, we found that sorption to so-called ''very slow'' sites also can be accomplished in a short period of time [8]. This occurred in sediment used for desorption experiments over an extended time period: desorption experiments with gas purging lasted several months.…”
Section: Introductionmentioning
confidence: 99%
“…Using a gas‐purge method, ten Hulscher et al [23] showed that decreases of F rapid for hexachlorobenzene and 2,4,4′‐trichlorobiphenyl in sediment followed a first‐order trend ( r 2 = 0.98), with a t 1/2 of 288 d. White et al [30] found that desorption and mineralization rates of phenanthrene in soils decreased by an order of magnitude after 50 or 60 d of aging and that plots of normalized rates of mineralization and desorption practically coincided. Therefore, the decrease of F rapid found for pyrethroids during the present study fell within the range found in the previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Characterizing the diffusive exchange of solutes between bulk water in an aquifer and water in the intragranular pores of the solid phase is still challenging despite decades of study. For organic solutes, the exchange is complicated by such issues as partitioning into various kinds of organic matter [ Huang et al , 2003; Warren et al , 2003; Ten Hulscher et al , 2005], bioavailability and biological activity [ Reichenberg and Mayer , 2006], and nonlinear isotherms [ McGinley et al , 1996; Ran et al , 2002]. Exchange of inorganic solutes such as contaminant uranium is complicated by multiple redox states, precipitation in multiple minerals, and interaction with other solutes [ Zachara et al , 2007; Liu et al , 2008].…”
Section: Introductionmentioning
confidence: 99%